PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PKN KELAS IV UPT SD NEGERI 060923 MEDAN - Donita, Harjanah; Juwita, Putri; Mesy Pertiwi, Amanda; Syafitri, Devilia; Naila Umi Kalsum Armaini, Azizah; Permata Sari, Winda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students’ learning outcomes in Civic Education on the topic of Lingkunganku through the implementation of the Discovery Learning model for fourth grade students at UPT SD Negeri 060923 Medan. This research employed Classroom Action Research conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The research subjects were all fourth grade students. Data were collected through learning outcome tests, observations of teacher and student activities, and documentation. Data analysis was carried out using descriptive quantitative methods to identify improvements in learning outcomes and descriptive qualitative methods to describe learning activities. The results showed that the implementation of the Discovery Learning model effectively improved students’ learning outcomes and learning engagement. In the initial condition, only 45% of students achieved learning mastery. After the implementation of actions in Cycle I, learning mastery increased to 65%, and further improved to 85% in Cycle II. In addition to the improvement in learning outcomes, students’ activity and participation in the learning process also increased, as indicated by active involvement in discussions, the ability to express opinions, and collaboration among students. Based on these findings, it can be concluded that the Discovery Learning model is effective in improving learning outcomes in Civic Education on the topic of Lingkunganku for fourth grade students and supports the creation of active, meaningful learning in accordance with the principles of the Merdeka Curriculum.